Theoretical bases of optimization of processes and technologies in systems power transformations - Кравченко, О.В.; Суворова, И.Г.; Суворов, Н.П. (Eastern-European Journal of Enterprise Technologies, 2010)
It is set by the authors, that on the basis of correlation it is possible to provide optimization of complex energy-transducing processes on the whole. As integral presentation of energy-transducing processes is extraordinarily difficult, so turning to presentation of processes as the generalized Fourier series, it is possible to simplify procedure of optimization to a great extent, investigating its separate elements.